2021
DOI: 10.12688/f1000research.51297.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of snail mucus on angiogenesis during wound healing

Abstract: Background: Angiogenesis is the process through which new blood vessels are formed from existing ones. This process plays an important role in supplying the oxygen and nutrients needed for cellular metabolism and eliminating cell debris during wound healing. Snail mucus can bind to several factors that stimulate angiogenesis, including vascular endothelial growth factor, platelet-derived growth factor, and fibroblast growth factor. The aim of this study is to observe changes in angiogenesis during the healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Snail mucus is an attractive natural substance that is increasingly used in cosmetic creams due to its emollient, moisturizing, protective, and reparative properties. Rosanto et al [ 5 ] investigated the wound healing effect upon using different concentrations of snail mucus after the daily application of SM gel. It was concluded that topical application of 48% and 96% snail mucus gel increased the angiogenesis during the wound healing process in Wistar rat skin.…”
Section: Introductionmentioning
confidence: 99%
“…Snail mucus is an attractive natural substance that is increasingly used in cosmetic creams due to its emollient, moisturizing, protective, and reparative properties. Rosanto et al [ 5 ] investigated the wound healing effect upon using different concentrations of snail mucus after the daily application of SM gel. It was concluded that topical application of 48% and 96% snail mucus gel increased the angiogenesis during the wound healing process in Wistar rat skin.…”
Section: Introductionmentioning
confidence: 99%
“…The process of stabilization and maturation of new blood vessels that is formed is also influenced by the presence of pericite cells in the walls of the blood vessels. A decrease in angiogenesis occurs due to selective apoptotic processes of new blood vessels that do not have pericits [4,18,19]. This raises the possibility that the 10% kirinyuh leaf extract gel also plays a decrease in the end of the proliferation phase on day 7.…”
Section: Discussionmentioning
confidence: 99%
“…Wounds cause loss of tissue continuity that causes the wound area to be deprived of oxygen and nutrients that are essential for healing [3]. Angiogenesis is an important step in the wound healing process because it will overcome the condition [4]. In general, angiogenesis is divided into three phases: initiation, invasion and maturation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation